Crystal structure, Hirshfeld surface analysis and spectroscopic characterization of the di-enol tautomeric form of the compound 3,3′-[(2-sulfanylidene-1,3-dithiole-4,5-diyl)bis(sulfanediyl)]bis(pentane-2,4-dione) - Keysha T. Cordero Giménez; Victoria Y. Soto Díaz; Jean C. González Espiet; Alexis Lavín Flores; Jesbaniris Bas Concepción; Kevin E. Rivera Cruz; Dara L. Rodríguez Ayala; Dalice M. Piñero Cruz (Acta Crystallographica Section E: Crystallographic Communications, 2020)
The reaction between [TBA]2[Zn(dmit)2] and 3-chloro-2,4-pentanedione yielded single crystals of the title compound, (3E,3′E)-3,3′-[(2-sulfanylidene-1,3-dithiole-4,5-diyl)bis(sulfanediyl)]bis(4-hydroxypent-3-en-2-one), C13H14O4S5, after solvent evaporation. The title compound crystallizes in the triclinic space group P\overline{1} with two molecules related by an inversion center present in the unit cell. The central thione ring moiety contains a carbon–carbon double bond covalently linked to two sulfoxide substituents located outside of the plane of the ring. The S—C—C—S torsion angles are −176.18 (8) and −0.54 (18)°. Intramolecular hydrogen bonds occur within the two dione substituents (1.67–1.69 Å). Adjacent asymmetric units are linked by C—H...S (2.89–2.90 Å), S...S [3.569 (1) Å] and O...H [2.56–2.66 Å between non-stacked thione rings] short contacts.